Revaluation of Vernacular Architecture in a Hot Humid Climate in Villa Rica-Peru: A Study of Thermal Comfort Compared to Confined Masonry - Castro Barrientos, Nahomi Lynn (2024)
Thermal comfort is a fundamental aspect in the quality of life of users in homes. The vernacular architecture of the Peruvian jungle, represented by malocas (wooden houses), is characterized by natural ventilation and shading elements that allow greater thermal comfort in these hot and humid climates. However, the preference for confined masonry houses is gradually displacing this valuable construction tradition, leading to the loss of recognition and appreciation of the benefits of the vernacular architecture of the Peruvian jungle. In Villa Rica, wooden housing and confined masonry housing are two common options in housing construction, but their thermal behavior is different. Since the choice of construction material can significantly influence the level of thermal comfort. The present research seeks to evaluate and compare thermal comfort in wooden and confined masonry homes, using direct measurements and analysis, with international standards such as ASHRAE 55 and EN-16798 to analyze the Predicted Mean Vote (PMV) and Predicted Percentage Dissatisfied indices. (PPD) and with simulation tools such as CBE Thermal Comfort Tool and Rayman to model and calculate the physiological equivalent temperature (PET) and the standard effective temperature (SET) which are indicators of thermal sensation, in order to determine the revaluation of the vernacular architecture.